Evaluation of the Effect of κ-casein Gene Polymorphism in Milk Powder on the Technological Properties of Acid-Induced Milk Gels - Alexandr G. Kruchinin; Svetlana N. Turovskaya; Elena E. Illarionova; Alana V. Bigaeva (Техника и технология пищевых производств, 2021)
Introduction. Yoghurt has become one of the most popular acid-induced dairy products in the world. Consumers see yoghurt not only as a tasty, protein-rich, and calcium-fortified dessert, but also as a product that improves intestinal microflora and prevents obesity, metabolic syndrome, type II diabetes, and cardiovascular diseases. The stability of the structure and consistency of yoghurt directly depend on the composition and properties of raw materials, including genetic and technological factors and compliance with temperature storage conditions. Yoghurt formulations include various dairy raw materials, e.g. milk powder. The research objective was to assess the effect of κ-casein gene polymorphism in milk powder on the technological properties of acid-induced milk gels when simulating different temperature storage conditions. Study objects and methods. The research featured yoghurt samples prepared from milk powder of CSN3 gene (AA and BB). Model systems of yoghurt were prepared from dry bulk milk, mixed by mass fraction of protein in the ratio of AA2:BB2 as 75:25, 50:50, and 25:75%, respectively. The experiment involved standard methods, optical methods, dynamic viscometry, and PCR-RFLP. Results and discussion. As the mass fraction of BB dry bulk milk increased, the structural and mechanical properties, dimensional stability, and surface tension increased, too. As the storage temperature fell from 4 ± 2 to 12 ± 2°C, the structural and mechanical properties, dimensional stability, surface tension, and moisture-holding ability decreased while maintaining the previously established dependencies. The CSN3 gene polymorphism proved to have no effect on the curd tension after fermentation. Significant differences between the allelic variants AA and BB became obvious only after complete cooling and structuring of the product. Conclusion. The obtained experimental results and the analysis of related publications suggested an indirect effect of the κ-casein gene polymorphism on the structural and mechanical properties, associated with a genetic effect on the average diameter of casein micelles in the original milk and the resulting biochemical and isothermal processes. The research made it possible to assess the effect of the CSN3 gene polymorphism on the technological properties of dry milk during its processing into fermented milk products.